Is early full weight bearing safe following locking plate ORIF of distal fibula fractures? - Michael Zyskowski; Markus Wurm; Frederik Greve; Sebastian Pesch; Francesca von Matthey; Patrick Pflüger; Moritz Crönlein; Peter Biberthaler; Chlodwig Kirchhoff (BMC Musculoskeletal Disorders, 2021)
Abstract Background In the modern western world appraisal of economical points such as treatment and disability after trauma present a financial burden. In this context open reduction internal fixation techniques allowing for early full weight bearing might not only improve the clinical outcome but also shorten the period of disability in working life. The aim of the study was to analyze whether ORIF of ankle fractures using either a standard semitubular plate or a new polyaxial locking plate system result in a better clinical outcome. Methods In this prospective study, all patients with distal fibula fractures (AO 44 B1.1, B1.2, B1.3), with indication for surgery were included. Patients were randomized to either the DePuy Synthes® one-third semitubular plate (Group I) or NEWCLIP TECHNICS, Active Ankle® polyaxial locking plate (Group II). Primary outcome parameter was function of the ankle joint, assessed by the Olerud and Molander ankle score, Foot and Ankle outcome score and Karlsson and Peterson Scoring System for Ankle function. Secondary outcome parameter were postoperative complications. Superficial wound infection, delayed wound healing, mechanically prominent implant, skin irritations were considered as minor and deep wound infection, material loosening, loss of reduction were regarded as major complications requiring revision surgery. Clinical and radiological follow-up were performed 6 and 12 weeks, 6 months and 1 year postoperatively. Results Fifty-two patients (31 W/21 M) with a mean age of 43 yrs. (range 22–64 yrs.) were enrolled. Seven patients (13.5%) were excluded, so that 45 patients were available for follow up. Twenty-five patients were treated with DePuy Synthes® one-third semitubular plate (55.6%; group I) while 20 patients received an anatomically preformed polyaxial locking plate (44.4%, group II). Four minor complications occurred in Group I (16%) compared to two minor complications in group II (10%). Significant better clinical results regarding OMAS (p < 0.02, < 0.04), KPSS (p < 0.04) and FAOS (p < 0.02, < 0.03) were observed 6 and 12 weeks after surgery in group II. Conclusions The results of the presented study demonstrate a significant better clinical functional outcome in the early postoperative follow-up in patients treated with a polyaxial locking plate. Furthermore, our data show that ORIF using polyaxial locking plates in combination with an early postoperative weight bearing presents a safe, stable treatment option for ankle fractures so that patients benefit especially in the early stages of recovery. Trial registration Registered 20 April 2020, retrospectively on ClinicalTrails.gov ( NCT04370561 ).